2022
DOI: 10.3390/jmse10121843
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Genetic Segregation among Meagre (Argyrosomus regius) Atlantic Spawning Areas

Abstract: The meagre Argyrosomus regius, one of the largest sciaenidae in the world, is a valuable resource for fisheries and aquaculture. Despite its socioeconomic relevance, knowledge about population dynamics and wild stocks is still scarce, and conservation risks are associated with overexploitation. Two genetic distinct groups, one in the North Atlantic Ocean and one in the eastern Mediterranean Sea, were identified by previous studies. However, little is known about the genetic structure of the Atlantic group, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Until recently, information on meagre population structure and stock connectivity remained scarce and mostly based on indirect sources such as fisheries landings [ 24 ] and otolith geochemical signatures [ 46 ]. To date, only three studies have conducted DNA analyses to infer its population structure: Haffray et al [ 28 ] using 11 microsatellites and, more recently, Almeida et al [ 29 ] relying on 15 microsatellite loci and Abecasis et al [ 30 ] using a more powerful set of genome-wide SNP-genotyping and mitochondrial DNA. Although all three studies have reported an unexpectedly high degree of genetic differentiation between meagre populations (not only between the Atlantic and Mediterranean populations, but also within the Atlantic), our large movement and low residency data provide strong evidence against the hypothesis of restricted adult dispersal/movement as a mechanism for genetic isolation, as previously speculated [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, information on meagre population structure and stock connectivity remained scarce and mostly based on indirect sources such as fisheries landings [ 24 ] and otolith geochemical signatures [ 46 ]. To date, only three studies have conducted DNA analyses to infer its population structure: Haffray et al [ 28 ] using 11 microsatellites and, more recently, Almeida et al [ 29 ] relying on 15 microsatellite loci and Abecasis et al [ 30 ] using a more powerful set of genome-wide SNP-genotyping and mitochondrial DNA. Although all three studies have reported an unexpectedly high degree of genetic differentiation between meagre populations (not only between the Atlantic and Mediterranean populations, but also within the Atlantic), our large movement and low residency data provide strong evidence against the hypothesis of restricted adult dispersal/movement as a mechanism for genetic isolation, as previously speculated [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic studies have unveiled an unexpectedly high degree of population differentiation not only between the Atlantic and Mediterranean, but also between the West and South coasts of the Iberian Peninsula [ 28 , 29 ]. More recently, Abecasis et al [ 30 ] confirmed this populational subdivision through a multi-disciplinary approach, combining DArT sequencing and mitochondrial DNA analysis with biotelemetry and biophysical models.…”
Section: Introductionmentioning
confidence: 99%